Glucose-insulin-potassium alleviates uterine cramping pain following cesarean delivery: A randomized, controlled trial - Yang, Guiying; Cui, Yu; Bao, Xiaohang; Wu, Zhuoxi; Chen, Qin; Chen, Feng; Liu, Wenjun; Wang, Mingming; Luo, Li; Li, Hong (Frontiers in Surgery, 2023)
Objectives To explore the effect of glucose-insulin-potassium (GIK) therapy on uterine cramping pain (UCP) following cesarean delivery (CD). Design Single-center, randomized controlled study. Setting Second Affiliated Hospital of Army Medical University, Chongqing, China. Participants A total of 140 women, aged 20–40 years, who underwent CD with a transverse incision were randomly assigned to the GIK (P) or control (C) groups in a 1:1 ratio. Interventions GIK was intravenously administered to patients in Group P. Patients in Group C received normal saline (NS). After umbilical cord clamping, oxytocin was administered intravenously. The same GIK and NS regimens were administered on postoperative days 1 and 2, followed by oxytocin 10 min later. Primary and secondary outcome measures Following oxytocin administration, UCP was assessed using the visual analog scale (VAS), and the maximum VAS score (primary outcome) was recorded. Results Patients in Group P had significantly lower maximum VAS scores than those in Group C on postoperative days 1 (38.4 ± 21.1 vs. 52.3 ± 20.8, p < 0.001) and 2 (10 [0,30] vs. 30.5 [8.75,50], p < 0.001). Group P patients also had shorter pain duration on postoperative day 1 (39.6 ± 19.5 min vs. 50.6 ± 18.2 min, p = 0.001). Group P patients had a lower incidence of inadequate analgesia of UCP than Group C on days 1 (45.5% vs. 74.2%, p < 0.001) and 2 (10.6% vs. 47.0%, p < 0.001); the RRs for experiencing inadequate analgesia for UCP postpartum in Group P patients was 0.612 (95% CI: 0.454–0.826, p < 0.001) on day 1 and 0.226 (95% CI: 0.107–0.476, p < 0.001) on day 2. The absolute risk reduction (ARR) was 28.7%; thus number needed to treat (NNT) was 3 after rounding up. A subgroup analysis demonstrated that Group P patients undergoing repeat CD had lower maximum VAS scores for UCP on both postoperative days 1 and 2. Conclusion Our findings suggest that GIK can relieve UCP and shorten its duration. Our results provide information to facilitate the development of novel approaches for managing UCP. Clinical Trial Registration: This study was approved by the Medical Ethics Committee of Second Affiliated Hospital of Army Medical University (2020-109-01, 19/11/2020) and registered in the Chinese Clinical Trial Registry (http://www.chictr.org.cn, ChiCTR2100041607,01/01/2021).